BAHASA SEBAGAI IDENTITAS GENDER: STUDI KASUS PENGGUNAAN BAHASA DI MEDIA SOSIAL X - Hikmah, Elok Faiqotul (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to explore the use of language as a tool for gender identity formation on X social media. This research examines how users reflect gender identity through language, transcend traditional stereotypes, and utilize the flexibility of language in an online context. The research data are 20 public posts from X users analyzed using a descriptive qualitative approach. Language indicators, such as the use of emoticons, empty adjectives, and direct communication styles, were used to identify linguistic patterns based on the theories of Lakoff and Henley & Kramarae. The results showed that women are no longer limited to supportive communication styles, but rather use assertive, harsh, or sarcastic language, while men have begun to adopt more emotional and aesthetic communication styles. The anonymity and flexibility of language on X social media allows users to experiment with gender identity, creating a more fluid and inclusive space. The findings contribute to sociolinguistic studies by highlighting the role of social media in shaping new gender identities in the digital age. It shows how online contexts enable linguistic interactions that transcend traditional gender boundaries, creating more dynamic identities.